Solder alloy, solder paste, solder ball, preformed solder, solder joint, in-vehicle electronic circuit, ECU electronic circuit, in-vehicle electronic circuit device, and ECU electronic circuit device

CN123036183APending Publication Date: 2026-11-03SENJU METAL IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202580023006.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-02-04
Filing Date
2025-02-03
Publication Date
2026-11-03

Smart Images

  • Figure CN123036183A_ABST
    Figure CN123036183A_ABST
Patent Text Reader

Abstract

The present application provides a soft solder alloy, a solder paste, a solder ball, a preformed soft solder, a brazed joint, an in-vehicle electronic circuit, an ECU electronic circuit, an in-vehicle electronic circuit device, and an ECU electronic circuit device, which have a low melting point, a high shear strength, and a proper failure mode. The soft solder alloy has an alloy composition, in mass %, of Ag: 2.0-3.6%, In: 1.0-5.0%, Sb: 3.0-5.0%, Fe: 0.001-0.030%, Co: 0.0000% or more and 0.0500% or less, and the balance being Sn. Preferably, the alloy composition further contains, in mass %, at least one of Zr, Ge, Ga, P, As, Pb, Zn, Mg, Cr, Ti, Mo, Pt, Pd, Au, Al, and Si, in a total amount of 0.100% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to solder alloys, solder paste, solder balls, preformed solder, brazed joints, automotive electronic circuits, ECU electronic circuits, automotive electronic circuit devices, and ECU electronic circuit devices. Background Technology

[0002] Automobiles are equipped with electronic circuits (hereinafter referred to as "on-board electronic circuits") that have electronic components soldered onto printed circuit boards. On-board electronic circuits are used to electrically control the engine, power steering, brakes, and other systems, and are crucial safety components for vehicle operation. In particular, the on-board electronic circuits called ECUs (Engine Control Units), which control the vehicle's electronic circuits to control fuel consumption, must be able to operate stably and without failure for extended periods. Due to the expanding applications, these on-board electronic circuits are installed in parts subjected to various external loads such as impacts and vibrations.

[0003] Since the 1980s, Sn-Ag solder alloys, as alternatives to Sn-Pb solder alloys, have been considered as solder alloys for use in engine compartments. Sn-Ag solder alloys have long been known for their versatility, as exemplified by their JIS designation A35. However, the fundamental positioning of Sn-Ag solder alloys is considered to be as lead-free solder alloys, corresponding to Sn-Pb solder alloys, and this has been further explored.

[0004] Furthermore, when Sn-Ag solder alloys are joined with Cu electrodes, since Cu is almost insoluble in Sn, a coarse CuSn intermetallic compound layer forms at the bonding interface between the Cu diffusing from the electrode and the Sn in the solder alloy. Consequently, the large amount of Ag3Sn precipitation makes the solder alloy brittle, raising various concerns. Therefore, various explorations have been conducted in the past regarding Sn-Ag solder alloys that will not break even under harsh operating conditions.

[0005] In Patent Document 1, the alloy composition of a Sn-Co solder alloy, incorporating Sb, Bi, In, Ag, and Ga, was explored to improve the tensile strength of the solder alloy. It has been revealed that the solder alloy described in the same document contains Co, which disperses fine CoSn and CoSn2 within the Sn matrix, contributing to improved tensile strength. Furthermore, the addition of elements such as Sb has been explored to lower the melting point.

[0006] Patent document 2 discloses a Sn-Ag-Sb-Ni-Bi-Co solder alloy that suppresses porosity and inhibits crack initiation even after thermal cycling tests. The same document explains that the absence of Cu reduces the melt viscosity, thus suppressing porosity. Furthermore, the same document also discloses that the presence of Ni, even without Cu, inhibits excessive Cu diffusion, thereby suppressing crack propagation.

[0007] Existing technical documents

[0008] Patent documents

[0009] Patent Document 1: Japanese Patent Application Publication No. 6-344180

[0010] Patent Document 2: Japanese Patent Application Publication No. 2018-1179 Summary of the Invention

[0011] The problem the invention aims to solve

[0012] As mentioned above, the inventions described in Patent Documents 1 and 2 achieve improved tensile strength of the solder alloy, suppress porosity, and improve thermal cycling resistance. Furthermore, Patent Document 1 explores methods to lower the melting point.

[0013] However, these evaluations alone are insufficient for soft solder alloys used in automotive electronic circuits. For example, in automotive electronic circuits, when a car carrying the electronic circuits travels on rough roads, it will be subjected to stresses from external impacts and vibrations. Therefore, exhibiting high shear strength, such as preventing the brazed joint from breaking, is extremely important for brazed joints.

[0014] Furthermore, even if a brazed joint is formed that is difficult to break, it will eventually fracture if stress is continuously applied. This continuous stress is believed to be caused by exposure to environments with drastic temperature differences. This is due to the differences in the coefficients of thermal expansion of the electrodes, the intermetallic compounds formed at the joint interface, and the bulk materials. In this case, the failure mode indicating the fracture site cannot be at the joint interface. Since the joint interface is bonded to the electrodes, it is not easy to alleviate stress at the joint interface. However, the physical and electrical loads are mainly applied to the joint interface of the brazed joint. Therefore, it is believed that using a more easily deformable bulk material to alleviate stress can suppress failure.

[0015] However, patent documents 1 and 2 make no mention of shear strength and failure modes, making it difficult to say that they reflect the actual situation in the use of brazed joints. Since brazed joints are used to electrically connect substrates and electronic components, breakage at the joint interface should be avoided as much as possible.

[0016] Therefore, patent documents 1 and 2 completely fail to discuss shear strength and failure mode, which are important characteristics for brazed joints. It is hoped that even Cu-free solder alloys can still exhibit these properties. However, with the advancement of automotive electrification in recent years, and considering the continued increase in the number of substrates mounted, it is urgent to develop solder alloys that exhibit these properties. Furthermore, given the heat resistance of electronic components, it is also desirable to exhibit a melting point similar to that of conventional alloys.

[0017] Therefore, the objective of this invention is to provide solder alloys, solder pastes, solder balls, preformed solders, brazed joints, automotive electronic circuits, ECU electronic circuits, automotive electronic circuit devices, and ECU electronic circuit devices that have low melting points, high shear strength, and appropriate failure modes.

[0018] Solution for solving the problem

[0019] The inventors further investigated the solder alloys disclosed in Patent Documents 1 and 2. The findings indicate that the shear strength of the solder alloys disclosed in these two documents—the Sn-Ag-In-Sb-Co-Ga solder alloy of Example 5 in Patent Document 1, the Sn-Ag-In-Sb-Co-Ni-Bi solder alloy of Example 19 in Patent Document 2, and the Sn-Ag-Sb-Co-Fe-Ni-Bi solder alloy of Example 24 in Patent Document 2—is similar to that of conventional solder alloys, and there is room for improvement.

[0020] These solder alloys may not have an alloy composition designed to improve shear strength. It should be understood that, generally speaking, even if the content of one component in a solder alloy is different, the overall properties will be different. A combination of alloying elements with a specific content is considered as a whole for technical evaluation.

[0021] Therefore, the inventors conducted a detailed investigation into suppressing the rise in melting point and improving shear strength and failure mode. Here, Patent Document 1 explains that adding Ag, In, Sb, and Ga to the Sn-Co solder alloy can lower the melting point. However, since the melting point varies significantly depending on the content of these elements, the composition described in Example 5 of Patent Document 1 may not be suitable.

[0022] Furthermore, Patent Document 1 discloses the addition of Co to improve tensile strength. However, it does not discuss improving shear strength. Moreover, when the tensile strength of the solder alloy is increased beyond what is necessary, the failure mode becomes the joint interface. Therefore, it is speculated that adding Co to the Sn-Ag-In-Sb-Co-Ga solder alloy is not ideal.

[0023] Patent Document 2 states that porosity can be suppressed as long as Ni and Co are within a certain range. Therefore, based on the description in Patent Document 2, the coexistence of Co and Ni can achieve the desired effect. Therefore, based on the observation that the alloy composition of Patent Document 1 results in low shear strength and an inappropriate failure mode, it can be inferred that adding Ni in Patent Document 2 is also not ideal.

[0024] Furthermore, Patent Document 2 states that thermal shock resistance can be maintained when the Bi content is below a certain amount. However, in Patent Document 2, since Bi is dissolved in Sn at a concentration of about 3%, the tensile strength of the solder alloy is increased by the solid solution strengthening of Sn, making the failure mode the joint interface.

[0025] Therefore, based on the above-mentioned insights, the inventors have focused on the Sn-Ag-In-Sb solder alloy obtained by excluding Ni, Co, and Bi from the additive elements added to Sn, as described in Patent Documents 1 and 2. Furthermore, in order to improve the shear strength of the solder alloy and achieve a bulk failure mode, the inventors have further explored in detail the selection of additive elements and the content of Ag, In, and Sb.

[0026] First, to ensure an appropriate failure mode, the growth of intermetallic compounds at the bonding interface must be suppressed in solder alloys that do not contain Cu or Ni. Intermetallic compounds grow due to the diffusion of Cu from the electrode towards the solder alloy. Here, the intermetallic compounds are mainly composed of compounds of Sn and Cu. Therefore, a coarse intermetallic compound layer at the interface between the solder alloy and the electrode can easily lead to an inappropriate failure mode.

[0027] Therefore, focusing on interfacial modification through the inclusion of Fe, the content of additive elements in Sn-Ag-In-Sb-Fe solder alloys was investigated in detail. The results suggest that only when the content of the additive elements is within a specific range can the shear strength be improved and the failure mode optimized.

[0028] The present invention, which is based on these insights, is as follows.

[0029] (0) A soft solder alloy, characterized in that, by mass % Ag: 2.0~3.6%, In: 1.0~5.0%, Sb: 3.0~5.0%, Fe: 0.0010~0.0300%, Co: more than 0.0000% and less than 0.0500%, with the balance being Sn.

[0030] (1) A soft solder alloy, characterized in that it has an alloy composition in terms of mass% Ag: 2.0~3.6%, In: 1.0~5.0%, Sb: 3.0~5.0%, Fe: 0.0010~0.0300%, Co: 0% or more and 0.050% or less, with the balance being Sn.

[0031] (2) The solder alloy as described in (0) or (1) above, wherein the alloy composition (solder alloy) further contains at least one of Zr, Ge, Ga, P, As, Pb, Zn, Mg, Cr, Ti, Mo, Pt, Pd, Au, Al and Si in a total of 0.100% or less by mass%.

[0032] (3) The solder alloy as described in any one of (0) to (2) above, wherein the alloy composition (solder alloy) satisfies the following formulas (1) and (2).

[0033]

[0034] In equations (1) and (2) above, Ag, In, Sb and Fe are the contents of the aforementioned solder alloy in terms of mass%.

[0035] (4) A solder paste having a solder powder comprising a solder alloy comprising any one of (0) to (2) above.

[0036] (5) A solder ball comprising any one of (0) to (2) above.

[0037] (6) A preformed solder comprising any one of (0) to (2) above.

[0038] (7) A brazing joint having any one of the above (0) to (2) solder alloys.

[0039] (8) An on-board electronic circuit, characterized in that it has a solder alloy as described in any one of (0) to (2) above.

[0040] (9) An ECU electronic circuit, characterized in that it has a solder alloy as described in any one of (0) to (2) above.

[0041] (10) An in-vehicle electronic circuit device, characterized in that it comprises the in-vehicle electronic circuit described in (8) above.

[0042] (11) An ECU electronic circuit device, characterized in that it comprises the ECU electronic circuit described in (9) above. Attached Figure Description

[0043] Figure 1 This shows an optical microscope image of the sample after the shear strength was measured. Figure 1 (a) is Example 14. Figure 1 (b) is Example 2. Figure 1 (c) is Comparative Example 3. Detailed Implementation

[0044] The present invention will be described in more detail below. In this specification, unless otherwise stated, "%" in relation to the composition of the solder alloy means "mass %".

[0045] 1. Soft solder alloy

[0046] (1) Ag: 2.0~3.6%

[0047] Ag contributes to improved shear strength, appropriate failure modes due to Ag3Sn precipitation, and lower melting point. When the Ag content is less than 2.0%, the amount of compound precipitated is low, resulting in reduced shear strength. The lower limit of Ag content is 2.0% or more, preferably 2.5% or more, more preferably 2.7% or more, and even more preferably 3.0% or more.

[0048] On the other hand, when the Ag content exceeds 3.6%, it becomes hypereutectic, resulting in the excessive precipitation of Ag3Sn, which excessively increases the strength of the bulk, thus making the interface the failure mode. Furthermore, since the failure mode is the interface, the shear strength decreases. The upper limit of the Ag content is 3.6% or less, preferably 3.5% or less, and more preferably 3.4% or less.

[0049] (2) In: 1.0~5.0%

[0050] In helps to improve shear strength and optimize the failure mode. When the In content is less than 1.0%, the wettability is reduced, resulting in insufficient wetting and spreading, and the solid solution strengthening effect is insufficient, leading to poor shear strength and an inappropriate failure mode. The lower limit of the In content is 1.0% or more, preferably 1.5% or more, more preferably 2.0% or more, even more preferably 2.5% or more, and particularly preferably 3.0% or more.

[0051] On the other hand, when the In content exceeds 5.0%, the melting point increases due to the large amount of compound precipitation. Furthermore, there are concerns about increased bulk strength leading to damage at joint interfaces or parts. The upper limit for the In content is 5.0% or less, preferably 4.5% or less, more preferably 4.0% or less, and even more preferably 3.5% or less.

[0052] (3) Sb: 3.0~5.0%

[0053] Sb helps to improve shear strength and optimize the failure mode. When the Sb content is less than 3.0%, the shear strength is poor due to insufficient solid solution strengthening of Sn and precipitation strengthening of Sn-Sb compounds. The lower limit of Sb content is 3.0% or more, preferably 3.5% or more, more preferably 3.6% or more, further preferably 3.8% or more, particularly preferably 3.9% or more, and most preferably 4.0% or more.

[0054] On the other hand, when the Sb content exceeds 5.0%, the shear strength is poor due to the formation of coarse SnSb compounds. Furthermore, wettability deteriorates, and the failure mode becomes interface or part failure, which is undesirable. The upper limit of the Sb content is 5.0% or less, preferably 4.8% or less, more preferably 4.6% or less, further preferably 4.5% or less, particularly preferably 4.3% or less, and most preferably 4.1% or less.

[0055] (4) Fe: 0.0010~0.0300%

[0056] Fe helps to improve shear strength and optimize the failure mode. When the Fe content is less than 0.0010%, the interfacial strengthening effect caused by the modification of the intermetallic compound layer formed at the interface is insufficient, resulting in poor shear strength and an unsuitable failure mode at the interface. The lower limit of the Fe content is 0.0010% or more, preferably 0.0050% or more, more preferably 0.0100% or more, further preferably 0.0150% or more, and particularly preferably 0.0200% or more.

[0057] On the other hand, when the Fe content exceeds 0.0300%, the bulk strength is excessively increased due to the precipitation of Sn-Fe compounds, which raises concerns about damage to the bonding interface. The upper limit of the Fe content is 0.0300% or less, preferably 0.0270% or less, and more preferably 0.0250% or less.

[0058] (5) Co: ≥0.0000% and ≤0.0500%

[0059] Co is any element that helps to suppress melting point rise, improve shear strength, and optimize the failure mode. In conventional solder alloys, based on the viewpoint of improved shear strength and optimized failure mode, it was considered that Co-free alloys were preferable. However, the addition of Co resulted in maintaining high shear strength, but the failure mode remained bulk. In Sn-Ag-In-Sb solder alloys, Co was thought to be finely dispersed as CoSn, etc. However, this did not achieve a sufficiently fine Sn alloy microstructure. Since Fe refines the Sn alloy microstructure in this system, it is hypothesized that if fine CoSn and other fine structures are dispersed, the overall alloy microstructure would further become finer. Therefore, in the solder alloy of the present invention, Co can exert a synergistic effect in the presence of Fe.

[0060] Furthermore, in the solder alloy of the present invention, since Co is an arbitrary element, high shear strength and appropriate failure mode can be maintained even when Co is not present. The lower limit of Co content is 0.0000% or more, preferably more than 0.0000%, more preferably 0.0010% or more, further preferably 0.0030% or more, particularly preferably 0.0060% or more, and most preferably 0.0080% or more.

[0061] On the other hand, when the Co content exceeds 0.0500%, the bulk strength is excessively increased due to the precipitation of Sn and Co compounds, thus the failure mode becomes the interface. Moreover, the melting point rises significantly due to the large amount of compound precipitation, and wettability deteriorates, thereby reducing shear strength. The upper limit of the Co content is 0.0500% or less, preferably 0.0300% or less, and more preferably 0.0100% or less.

[0062] (6) Balance: Sn

[0063] The balance of the solder alloy of the present invention is Sn. In addition to the elements mentioned above, unavoidable impurities may also be present. The presence of unavoidable impurities does not affect the aforementioned effects. It should be noted that in the present invention, when the Sn-Ag-In-Sb-Fe solder alloy contains Ni, SnNi will precipitate. Since the SnNi compound precipitates with the intermetallic compound formed at the interface as its nucleus, the intermetallic compound formed at the interface becomes thicker. As a result, the shear strength decreases. Therefore, it is preferable that Ni is not present in the present invention. Furthermore, if Bi coexists with In, a low-melting-point Sn-In-Bi phase is formed. Given creep deformation, since the low-melting-point phase has a low melting point that causes the room temperature environment to become a high-temperature environment, it is prone to creep deformation, resulting in a decrease in shear strength. Therefore, it is preferable that Bi is not present in the present invention.

[0064] (7) At least one of Zr, Ge, Ga, P, As, Pb, Zn, Mg, Cr, Ti, Mo, Pt, Pd, Au, Al and Si, totaling less than 0.100%.

[0065] The solder alloy of the present invention may contain at least one of the following elements as arbitrary elements, in a total amount of less than 0.100%, without impairing the effects of the present invention: Zr, Ge, Ga, P, As, Pb, Zn, Mg, Cr, Ti, Mo, Pt, Pd, Au, Al, and Si. Preferably, the total amount is less than 0.080%. The lower limit of the content is not particularly limited, but it is acceptable to be more than 0.0001%, and may be more than 0.001%.

[0066] Equations (8)(1) and (2)

[0067]

[0068] In equations (1) and (2) above, Ag, In, Sb and Fe are the contents of the solder alloy by mass%.

[0069] Formula (1) is a formula that takes into account the balance of additive elements in the solder alloy of the present invention. The solder alloy of the present invention can achieve low melting point, high shear strength and appropriate failure mode through the synergistic effect of each constituent element. Therefore, if the balance of all constituent elements other than Sn is further optimized, all the effects of the present invention can be further improved. In formula (1), the contents of Ag, In and Sb are about 10 to 100 times that of Fe. However, it is considered that their contribution to the solder alloy is equal. Therefore, in the present invention, in order to further improve low melting point, high shear strength and appropriate failure mode with a single composition, it is preferable to set the contents to be balanced.

[0070] Equation (2) takes into account the balance of In and Sb within the group, which would cause the shear strength to increase to the point of part failure if the upper limit is exceeded, and the balance of Ag and Fe within the group remaining at the interface failure site, and further considers the balance of the two groups. When equation (2) is satisfied, there is a case where the failure mode is further appropriated according to the alloy composition.

[0071] The lower limit of formula (1) is preferably 0.36 or more, more preferably 0.39 or more, further preferably 0.42 or more, even more preferably 0.43 or more, particularly preferably 0.44 or more, and most preferably 0.52 or more, 0.53 or more, 0.60 or more, 0.656 or more, 0.66 or more, 0.70 or more, 0.75 or more, 0.78 or more, 0.79 or more, 0.84 or more, 0.87 or more, and 0.88 or more. The upper limit of formula (1) is preferably 1.19 or less, more preferably 1.18 or less, even more preferably 1.09 or less, even more preferably 1.08 or less, particularly preferably 1.05 or less, and most preferably 1.02 or less, 0.91 or less, 0.92 or less, and 0.90 or less.

[0072] The lower limit of formula (2) is preferably 47 or more, more preferably 51 or more, further preferably 57 or more, even more preferably 68 or more, particularly preferably 69 or more, and most preferably 85 or more, 86 or more, 91 or more, 102 or more, 103 or more, 114 or more, 120 or more, 133 or more, 137 or more, 141 or more, 142 or more, 143 or more, 154 or more, and 160 or more. The upper limit of formula (2) is preferably 319 or less, more preferably 286 or less, even more preferably 285 or less, even more preferably 267 or less, particularly preferably 266 or less, and most preferably 257 or less, 240 or less, 229 or less, 228 or less, 213 or less, 206 or less, 205 or less, 200 or less, 192 or less, 183 or less, 182 or less, and 171 or less.

[0073] In the calculations of equations (1) and (2), the measured values ​​of the alloy composition shown in Tables 1 and 2 below are used, and the values ​​described in the tables are used. That is, in the calculations of equations (1) and (2), for the measured values ​​shown in Tables 1 to 3 below, all digits less than the significant figures are treated as 0. For example, when the measured Fe content is “0.0250” mass%, the Fe content used to calculate equations (1) and (2) is not in the range of 0.02505 to 0.02514%, but is treated as “0.025000…”. In equation (1), the result is calculated to the third decimal place, and the third decimal place is rounded to the second decimal place. In equation (2), the result is calculated to the first decimal place, and the first decimal place is rounded to the ones place.

[0074] In addition, when calculating equations (1) and (2) from the alloy composition specifically disclosed in the patent documents and other documents described in this specification, the same method shall be used.

[0075] As mentioned above, in an alloy, not all constituent elements function individually, but rather all constituent elements as a whole constitute a single entity. Therefore, it is rare for a single element to simultaneously exhibit all the superior effects. Thus, as stated above, in order to exhibit superior properties within the optimal content range of each constituent element, it is necessary to consider the constituent elements as a whole. In the soft solder alloy of the present invention, in order to satisfy all the requirements of low melting point, high shear strength, and appropriate failure mode at a higher level with a single composition, it is preferable to satisfy equations (1) and (2).

[0076] Furthermore, in the embodiments described later, a determination result of "◎" indicates that it is practically more preferred than "〇". Since "〇" is a better result than the past, it falls within the scope of the present invention and is treated as an example when other evaluation results are also excellent. Since "×" is a insufficient result in the present invention, it is outside the scope of the present invention and is treated as a comparative example.

[0077] 2. Solder paste

[0078] The solder paste of the present invention is a mixture of solder powder comprising the above-mentioned alloy composition and flux. The flux used in the present invention is not particularly limited as long as it can be soldered by common methods. Therefore, any flux appropriately mixed with commonly used rosin, organic acids, activators, thixotropic agents, and solvents is acceptable. The mixing ratio of the metal powder component and the flux component in the present invention is not particularly limited, but preferably the metal powder component is 70-90% by mass, and the flux component is 10-30% by mass.

[0079] 3. Solder ball

[0080] The solder alloy of the present invention can be used as solder balls. When used as solder balls, the solder alloy of the present invention can be manufactured using a drop-down method, a common method in the art. Furthermore, for solder balls, brazed joints can be manufactured by processing them using common methods in the art, such as mounting a solder ball onto an electrode coated with flux and joining them. The particle size of the solder balls is preferably 1 μm or more, more preferably 10 μm or more, further preferably 20 μm or more, and particularly preferably 30 μm or more. The upper limit of the particle size of the solder balls is preferably 3000 μm or less, more preferably 1000 μm or less, further preferably 800 μm or less, and particularly preferably 600 μm or less.

[0081] 4. Pre-formed soft solder

[0082] The solder alloy of the present invention can be used as a preform. Examples of preform shapes include washers, rings, granules, disks, strips, and wires.

[0083] 5. Brazed joints

[0084] The brazing joint of the present invention is suitable for connecting at least two or more components. The term "components to be joined" is not particularly limited as long as they are semiconductors, power modules, inverter products, etc., that use the soft solder alloy of the present invention for electrical connection, such as components, substrates, electronic parts, printed circuit boards, insulating substrates, heat sinks, lead frames, electrode terminals, etc.

[0085] The joining method using the solder alloy of the present invention can be performed according to common methods, such as reflow soldering. The melting temperature of the solder alloy during reflow soldering should preferably be about 20°C higher than the liquidus temperature. Furthermore, when joining using the solder alloy of the present invention, the alloy microstructure can be further refined by considering the cooling rate during solidification. For example, the brazed joint can be cooled at a cooling rate of 2-3°C / s or higher. These other joining conditions can be appropriately adjusted according to the alloy composition of the solder alloy.

[0086] 6. Vehicle electronic circuits, ECU electronic circuits, vehicle electronic circuit devices, ECU electronic circuit devices

[0087] As can be understood from the description to date, the solder alloy of the present invention suppresses melting point rise and exhibits an appropriate failure mode. Therefore, even when used in automotive applications exposed to harsh environments, i.e., vehicle-mounted applications, it can suppress the breakage of brazed joints without deviation. Therefore, due to these particularly significant characteristics, the solder alloy of the present invention is particularly suitable for soldering electronic circuits mounted in automobiles.

[0088] Therefore, the solder alloy of the present invention is more specifically used for soldering automotive electronic circuits or for soldering ECU electronic circuits, and achieves excellent results.

[0089] An "electronic circuit" is a system that uses electronic engineering to combine multiple electronic components, each with its own function, to perform a target function as a whole.

[0090] Examples of electronic components that constitute such electronic circuits include chip resistors, multi-gang resistors, QFPs, QFNs, power transistors, diodes, and capacitors. An electronic circuit assembled from these electronic components is mounted on a substrate, thus forming an electronic circuit device.

[0091] In this invention, the substrate constituting such an electronic circuit device, such as a printed circuit board, is not particularly limited. Its material is also not particularly limited, but heat-resistant plastic substrates (e.g., FR-4 with high Tg and low CTE) can be used as examples. The printed circuit board is preferably a printed circuit board whose Cu pad surface is treated with an organic compound such as an amine or imidazole (OSP: Organic Surface Protection).

[0092] 7. Other

[0093] The solder alloy of the present invention can be manufactured with low alpha radiation by using low alpha radiation materials as its raw materials. This low alpha radiation alloy can suppress soft errors when used for forming solder bumps around memory chips.

[0094] Example

[0095] Although the present invention is illustrated by the following embodiments, the present invention is not limited to the following embodiments.

[0096] To demonstrate the effectiveness of the present invention, the soft solder alloys described in Tables 1-3 were used to evaluate (1) melting point, (2) shear strength and (3) failure mode.

[0097] (1) Melting point

[0098] For the solder alloys shown in Tables 1-3, the temperatures were determined from the DSC curves. The DSC curves were obtained using a Seiko Instruments DSC (model: 6200) at an atmospheric temperature with a heating rate of 5°C / min. The liquidus temperature was determined from the obtained DSC curves and set as the melting point. When the melting point is below 232°C, reflow soldering can be performed at the same temperature as before. When the melting point is above 232°C, reflow soldering cannot be performed as before due to the high melting point.

[0099] (2) Shear strength

[0100] (2-1) Sample preparation

[0101] The solder alloys shown in Tables 1-3 were cast to produce solder sheets (diameter: 1 mm, thickness: 0.15 mm). Chip resistors were soldered to the Cu-OSP electrodes of the FR-4 substrate using a reflow oven (SNR-615: manufactured by Senju Metal Industries, Ltd.). 3216CR (CR32-114JV: manufactured by Hokuriku Electric Industries, Ltd.) was used as the chip resistor. The reflow profile was set at 220°C or higher for 40 seconds, with the peak temperature set at 245°C in a nitrogen atmosphere.

[0102] (2-2) Evaluation of shear strength

[0103] For samples prepared in this manner, a shear testing machine (STR-1000: manufactured by RHESCA) was used with a shear rate set to 6 mm / min to determine the shear strength. A shear strength of 84.0 N or higher was rated "◎". A shear strength of 70.0 N or higher but less than 84.0 N was rated "○". A shear strength less than 70.0 N was rated "×".

[0104] (3) Destruction Mode

[0105] The failure modes of the samples evaluated in "(2) Shear Strength" were observed using an optical microscope (VHX-5000: KEYENCE). Samples that failed as bulk were rated "◎". Samples that failed as bulk and as intermetallic compounds (IMC) at the interface were rated "〇". Samples that failed as intermetallic compounds at the interface were rated "×".

[0106] The evaluation results are shown in Tables 1-3.

[0107] [Table 1]

[0108]

[0109] [Table 2]

[0110]

[0111] [Table 3]

[0112]

[0113] As shown in Tables 1 and 2, in Examples 1 to 110, since the content of each constituent element was appropriate, all evaluations were practically tolerable. Furthermore, it can be seen that Examples 3 to 14, 16, 19, 22, 28 to 31, 37 to 48, 50, 54, 57, 66, 68 to 73, and 77 to 110, which satisfy equations (1) and (2), showed extremely excellent results in all evaluations. This result indicates that among practically tolerable results, there are also some significantly different and superior ones.

[0114] On the other hand, as shown in Table 3, Comparative Example 1, lacking In, Sb, and Fe, exhibited poor shear strength and an inappropriate failure mode. Comparative Example 2, with its low Ag content, also showed poor shear strength. Comparative Example 3, with its high Ag content, also exhibited poor shear strength and an inappropriate failure mode.

[0115] Comparative Example 4, lacking In, and Comparative Example 5, with a low In content, exhibited poor shear strength and an inappropriate failure mode. Comparative Example 6, with a high In content, also exhibited an inappropriate failure mode.

[0116] Comparative Example 7, due to its low Sb content and absence of Fe, exhibited poor shear strength and an inappropriate failure mode. Comparative Example 8, due to its low Sb content, also exhibited poor shear strength. Comparative Example 9, due to its high Sb content, also exhibited poor shear strength and an inappropriate failure mode.

[0117] Comparative Examples 10-12 exhibited poor shear strength and an inappropriate failure mode due to inappropriate Fe content. Comparative Example 13, with its high Co content, resulted in a significantly increased melting point, poor shear strength, and an inappropriate failure mode. Comparative Examples 14 and 15, each containing Ni or Bi, exhibited poor shear strength.

[0118] Figure 1 This shows an optical microscope image of the sample after the shear strength was measured. Figure 1 (a) is Example 14. Figure 1 (b) is Example 2. Figure 1 (c) is Comparative Example 3. For example, from... Figure 1 It is understood that the brazed joint of Example 14 fractured due to bulk failure. On the other hand, it is understood that in Example 2, the failure was due to intermetallic compounds at the joint interface and the bulk itself. Furthermore, it is understood that the brazed joint of Comparative Example 3 fractured due to intermetallic compounds at the joint interface. Therefore, it can be concluded that the failure mode in Example 14 is appropriate. The same result applies to other examples.

[0119] Industrial availability

[0120] The solder of the present invention can be used in vehicle electronic circuits such as ECUs, which are electronic circuits that control automobiles with computers to suppress fuel consumption, but it can also be used in consumer electronic devices such as personal computers and achieve excellent results.

Claims

1. A soft solder alloy, characterized in that, It has an alloy composition in terms of mass% as follows: Ag: 2.0~3.6%, In: 1.0~5.0%, Sb: 3.0~5.0%, Fe: 0.0010~0.0300%, Co: more than 0.0000% and less than 0.0500%, with the balance being Sn.

2. The solder alloy according to claim 1, wherein, The alloy composition further contains at least one of Zr, Ge, Ga, P, As, Pb, Zn, Mg, Cr, Ti, Mo, Pt, Pd, Au, Al and Si, in a total of less than 0.100% by mass.

3. The solder alloy according to claim 1 or 2, wherein, The alloy composition satisfies the following equations (1) and (2). In equations (1) and (2) above, Ag, In, Sb and Fe are the contents of the solder alloy by mass%.

4. A solder paste having a solder powder comprising a solder alloy as described in claim 1 or 2.

5. A solder ball comprising the solder alloy of claim 1 or 2.

6. A preformed solder comprising the solder alloy of claim 1 or 2.

7. A brazing joint having the soft solder alloy as described in claim 1 or 2.

8. A vehicle-mounted electronic circuit, characterized in that, It has the soft solder alloy as described in claim 1 or 2.

9. An ECU electronic circuit, characterized in that, It has the solder alloy as described in claim 1 or 2.

10. A vehicle-mounted electronic circuit device, characterized in that, It possesses the vehicle-mounted electronic circuit as described in claim 8.

11. An ECU electronic circuit device, characterized in that, It has the ECU electronic circuit as described in claim 9.

Citation Information

Patent Citations

  • Leadless solder alloy

    JP1994344180A

  • Lead-free solder alloy, electronic circuit board and electronic control device

    JP2018001179A